Implementation of Experimental Innovation Ecosystems as Tools for the Realisation of Sustainable Development: A Polish, Czech and Slovak Perspective - Majewski, Marcin (Publishing House of Wroclaw University of Economics and Business, 2025)
This chapter explores the role of experimental innovation ecosystems – specifically Real-World Laboratories and Living Labs in transforming the vision of sustainable development into actionable solutions. Focusing on Poland, Czechia and Slovakia, it highlights how these collaborative platforms bring together academia, industry, public policy, and civil society to co-create, test, and refine responses to complex sustainability challenges. The study identifies the core functions of Real-World Laboratories and Living Labs, including real-life experimentation, reflexive learning, stakeholder engagement, and capacity building, as crucial drivers for embedding sustainable practices into real-world settings. By bridging the gap between global sustainability goals and local action, these ecosystems foster new ways of working, learning, and innovating that help accelerate transitions toward a more sustainable and inclusive future.
Quote as: Majewski, M. (2025). Implementation of Experimental Innovation Ecosystems as Tools for the Realisation of Sustainable Development: A Polish, Czech and Slovak Perspective. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 47-60). Publishing House of Wroclaw University of Economics and Business.
Keywords: innovation; sustainable development; experimental innovation ecosystems; environmental economics